The Effectiveness of a Training Program in the light of School Accreditation Standards for Developing the Teaching Skills of Art Education Female- teachers - Ali, Badria Mohamed (Journal of Educational and Psychological Sciences, 2019)
The study aimed to determine the effectiveness of the training program in developing planning skill among Art Education teachers, determine the effectiveness of the training program in developing the implementation skill among Art Education teachers, determine the effectiveness of the training program in developing the assessment skill among Art Education teachers, and determine the effectiveness of the training program in developing the teaching skills among Art Education teachers. The problem of the study was identified the in the following main question: What is the effectiveness of the training program in light of the school accreditation standards in the development of teaching skills of Art Education teachers? And to answer the question, four hypotheses were formulated for the study. The hypotheses were tested by using the quasi-experimental approach to study the impact of the independent variable (training program in light of the school accreditation standards) against the dependent variable (Art Education teaching skills of Al-Baha Province teachers). The tools of the study were summative assessment and the training program, and after collecting the data processed by the arithmetic means (averages) and standard deviations, test (t), square (ETA), Black equation for rate uncovering, the sample of the study was randomly selected from the Art Education teachers in Al-Baha Province, consisted of (30) teachers (25%) of the total school community (120) teachers. The findings of this study showed statistically significant differences at the level of planning skill among Art Education teachers, for post-test, it showed statistically significant differences at the level of the implementation skill among Art Education teachers, for post-test, it showed statistically significant differences at the level of assessment skill among Art Education teachers, for post-test, it showed statistically significant differences in the overall grades for all teaching skills among Art Education teachers, parameters for post -test. In the light of the findings, the researcher recommended many recommendations: working on developing the teachers skills in the Ministry of Education in accordance with accurate professional standards that ensure improvement of teaching processes, dissemination of work culture according to the school accreditation standards for all school staff and employees to keep up with the developments and updates, take advantage of the current study tools in a way that is useful in improving the performance of Art Education male and female teachers.
Keywords: art education; secondary stage; teaching skills